Tuwim and Witkacy: Visual Translation of ’Kalinowe dwory’ - Polit, Paweł (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article offers a comparative analysis of a lost painting by Witkacy (know only from a photographic reproduction) and a poem by Julian Tuwim. Tuwim’s poem inspired Witkacy to create his work. The poem is used by the author as a model for interpreting philosophical aspects of Witkacy’s painterly composition, offering a concluding remark that the visual translation of the poem reflects Witkacy’s aesthetic philosophy. The article also provides an new way of reading Tuwim’s poetry in which the painterly aspect of his writing is being particularly exposed.